Duration of Postoperative Delirium Is an Independent Predictor of 6‐Month Mortality in Older Adults After Hip Fracture. Issue 7 (2nd June 2014) - Bellelli, Giuseppe; Mazzola, Paolo; Morandi, Alessandro; Bruni, Adriana; Carnevali, Lucio; Corsi, Maurizio; Zatti, Giovanni; Zambon, Antonella; Corrao, Giovanni; Olofsson, Birgitta; Gustafson, Yngve; Annoni, Giorgio
<x xml:space="preserve">Abstract</x> Objectives To evaluate the association between number of days with delirium and 6‐month mortality in elderly adults after hip fracture surgery. Design Prospective cohort study with 6‐month follow‐up. Setting Orthogeriatric Unit (OGU). Participants Individuals (mean age = 84.3 ± 6.4) admitted to the OGU between October 2011 and April 2013 with hip fracture (N = 199). Measurements Postoperative delirium (POD) was assessed daily using the Confusion Assessment Method algorithm and the Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition, Text Revision, criteria. Multivariable Cox regression models were used to evaluate the association between POD of and 6‐month mortality after surgery, after adjustment for covariates including age, prefracture residence, Katz activity of daily living score, New Mobility score, diagnosis of prefracture dementia, American Society of Anesthesiologists score, albumin serum levels, Charlson Comorbidity Index, and length of OGU stay. Results Fifty‐seven participants (28.6%) developed POD. In the 6‐month period after surgery, 35 (17.6%) participants died: 16 of 57 (28.1%) with POD and 19/ of 142 (13.4%) with no POD. The average duration of POD was 2.0 ± 3.2 days for participants who died and 0.7 ± 1.8 days for those who survived (P < .001). After adjusting for covariates, each day of POD in the OGU increased the hazard of dying at 6 months by 17% (hazard ratio = 1.17, 95% confidence interval = 1.07–1.28). Conclusion In older adults undergoing hip fracture surgery, duration of POD is an important prognostic factor for 6‐month mortality. Efforts to reduce duration of POD are therefore crucial for these individuals.